Micro-computed tomographic evaluation on the quality of single-cone obturation using a modified passive-deflation sealer injection needle: an in vitro study - Zhuo Chen; Nuo Chen; Yanling Yang; Wei Fan (BMC, 2024)
Abstract Objectives This study aimed to design a modified passive-deflation sealer injection needle and investigate its ability to improve obturation quality of single-cone technique through assessing the distribution of voids in root canals using micro-computed tomography (micro-CT). Materials and methods Forty-eight mandibular incisors were divided into eight groups (n = 6), according to the taper of root canal preparation (0.06 or 0.04), the needle used for sealer injection (modified or commercial iRoot SP injection needle), and the obturation method (iRoot SP sealer-only or single-cone obturation). After obturation, each specimen was scanned by micro-CT. The volumetric percentage and distribution of all voids were first analyzed and compared among groups, then the open and closed voids were separately analyzed and compared among single-cone obturation groups. Results Compared to commercial needle groups, modified needle groups showed much less voids, especially in the apical root canal part (P < 0.05). Besides, the modified needle groups produced much less open voids than commercial needle groups despite the root canal taper (P < 0.05). Conclusions The modified passive deflation sealer injection needle could effectively improve the quality of single-cone obturation through reducing intra-canal voids, especially open voids throughout the root canal, thus might possibly be developed as an effective intra-canal sealer delivering instrument.